2021
DOI: 10.29210/020211479
|View full text |Cite
|
Sign up to set email alerts
|

Analisis kerjasama sekolah dengan dunia usaha dan dunia industri dalam meningkatkan mutu lulusan sekolah menengah kejuruan

Abstract: This study aims to analyze the school's collaboration with industry and business community (DU/DI) in improving the quality of Vocational High School (SMK) graduates. This study applies a qualitative descriptive approach of case study design at SMK Negeri 3 Jayapura. The researcher as the key instrument of the research conducted an in-depth interview with principals, teachers/public relations, students, school committees, supervisors as well as industry and business community (DU/DI). Participatory observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Regulasi tersebut memberikan catatan penting bahwa keberadaan SMK bahkan lulusannya diharapkan dapat mendukung pertumbuhan ekonomi nasional yang dapat bekerja pada sektor DU/DI saat ini dan dalam menghadapi era global. Lulusan SMK dikatakan bermutu manakala terserap oleh DU/DI sesuai program keahlian bahkan dapat membuka lapangan kerja [2]. Sekolah Menengah Kejuruan (SMK) merupakan salah satu jenis pendidikan menengah yang menyiapkan calon tenaga kerja sesuai kebutuhan pasar kerja yang spesifik pada bidang keahlian tertentu.…”
Section: Pendahuluanunclassified
“…Regulasi tersebut memberikan catatan penting bahwa keberadaan SMK bahkan lulusannya diharapkan dapat mendukung pertumbuhan ekonomi nasional yang dapat bekerja pada sektor DU/DI saat ini dan dalam menghadapi era global. Lulusan SMK dikatakan bermutu manakala terserap oleh DU/DI sesuai program keahlian bahkan dapat membuka lapangan kerja [2]. Sekolah Menengah Kejuruan (SMK) merupakan salah satu jenis pendidikan menengah yang menyiapkan calon tenaga kerja sesuai kebutuhan pasar kerja yang spesifik pada bidang keahlian tertentu.…”
Section: Pendahuluanunclassified
“…The implementation of collaboration includes Memoranda of Understanding (MoU) with industries, curriculum alignment, industry visits and benchmarking, guest teachers, internships, On-the-Job Training (OJT), and the establishment of teaching factories. However, one of the practices of SMK and industry collaboration was found to be suboptimal in the research by Munthe and Mataputun (2021). Curriculum alignment and the expert teachers have not touched on the substantive aspects of industry practices and graduate absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The mandate of the teacher regulation above is expected to be a reference for every teacher in carrying out their duties, both at school and outside school, Law Number 20 of 2003 Article 18 states that vocational education is a secondary education that prepares students to work in certain fields (Pandipa, 2020). The presence of SMK is expected to prepare students: (1) enter certain jobs and develop a professional attitude, (2) have the provision and ability to choose a career, be able to compete, and be able to develop themselves, (3) become an independent middle-level workforce and/or fill the current and future needs of DU/DI (Munthe & Mataputun, 2021). What has been outlined in the regulation requires educators to work well, so that their graduates can benefit many people.…”
Section: Introductionmentioning
confidence: 99%
“…However, in several references there are still many teachers who have not carried out their duties properly, such as the results of research reported by (Helmi, 2015) that teacher performance shown in planning, implementation and evaluation is categorized as still lacking, even the results of the study (Munthe & Mataput, 2015). (Munthe & Mataputun, 2021) said that in general, SMK negeri 3 Jayapura has collaborated with Du/Di in improving the quality of graduates, but not maximally. The results of this empirical study provide a note that principals and teachers are not optimal in preparing, implementing the learning process expected of every SMK graduate, namely schools need to establish partnerships with the Business and Industrial World (DUDI).…”
Section: Introductionmentioning
confidence: 99%